2022
DOI: 10.1093/hr/uhac177
|View full text |Cite
|
Sign up to set email alerts
|

StMPK7 phosphorylates and stabilizes a potato RNA-binding protein StUBA2a/b to enhance plant defence responses

Abstract: Mitogen-activated protein kinase (MAPK) cascades play pivotal roles in regulating plant immunity. MAPKs usually transduce signals and regulate plant immunity by phosphorylating the downstream defence-related components. Our previous study indicates that StMPK7 positively regulates plant defence to Phytophthora pathogens via SA signalling pathway. However, the downstream component of StMPK7 remains unknown. In this study, we employed GFP-StMPK7 transgenic potato and performed immunoprecipitation-mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…N. benthamiana is an ideal model host plant to study the molecular mechanisms of immunity of solanaceous plants against oomycetes belonging to the Phytophthora genus (Du et al, 2021 ; Li et al, 2022 ; Matsukawa et al, 2013 ; Shibata et al, 2016 ; Zhang et al, 2021 ). In our cDNA‐VIGS screen in N. benthamiana , we tested in total 384 Agrobacterium colonies containing random TRV2 plasmids (unpublished data), and we found that VIGS driven by one Agrobacterium colony containing a TRV2 plasmid with an insert of which the nucleotide sequence matches with a N. benthamiana MAPKK gene ( Niben101Scf01249g04006 ) resulted in an enhanced susceptibility to P. infestans .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N. benthamiana is an ideal model host plant to study the molecular mechanisms of immunity of solanaceous plants against oomycetes belonging to the Phytophthora genus (Du et al, 2021 ; Li et al, 2022 ; Matsukawa et al, 2013 ; Shibata et al, 2016 ; Zhang et al, 2021 ). In our cDNA‐VIGS screen in N. benthamiana , we tested in total 384 Agrobacterium colonies containing random TRV2 plasmids (unpublished data), and we found that VIGS driven by one Agrobacterium colony containing a TRV2 plasmid with an insert of which the nucleotide sequence matches with a N. benthamiana MAPKK gene ( Niben101Scf01249g04006 ) resulted in an enhanced susceptibility to P. infestans .…”
Section: Resultsmentioning
confidence: 99%
“…According to the phylogenetic tree of solanaceous MAPKK proteins, we renamed this gene as NbMKK5. To (Du et al, 2021;Li et al, 2022;Matsukawa et al, 2013;Shibata et al, 2016;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of TaRZ1 in Arabidopsis also affects many genes related to plant growth and stress response (Xu et al., 2015 ). RBP StUBA2a/b also positively regulates plant defence against Phytophthora pathogens via the salicylic acid (SA) signalling pathway (Li et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%